Smart home: Monitoring Kondisi Cuaca Menggunakan Sensor Kelembapan dan Kecepatan Angin Berbasis Metode Fuzzy - Jefiza, Adlian; Fernanda, Heri; Firdaus, Fadli (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
Global warming has changed weather patterns in Indonesia, making it difficult to predict, and often the weather changes rapidly, such as sudden rain when the weather is hot. This study aims to overcome the problem of sudden weather changes by using a set of tools that can monitor humidity and wind speed based on the Internet of Things (IoT). This system uses an ESP32 microcontroller combined with a DHT22 sensor to measure humidity and an anemometer to measure wind speed. The collected data will be processed to produce an analysis of weather conditions using the fuzzy logic method and stored in Firebase for efficient data management. In addition, the user interface is designed based on Android Studio to facilitate real-time monitoring. The results of the study show that the developed system is able to provide accurate and reliable weather information, thus helping people plan their activities better.